2010
DOI: 10.1007/s10570-010-9413-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of amino acid modified cellulose surfaces using ToF-SIMS and XPS

Abstract: Cellulosic fibrous networks are modified using 3 different amino acids; small (Glycine, Gly), aliphatic (Leucine, Leu) and aromatic (Phenylalanine, Phe). The effect of amino acid functionality on chemical coupling to cellulose fibres in terms of their coverage and packing density are investigated. Different amino acid modified cellulose networks are characterised by using Time of Flight Secondary Ion Mass Spectrometry (ToF-SIMS) and X-ray Photoelectron Spectroscopy (XPS). The presence of amino acids is confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…166 In literature, ToF-SIMS has been used to verify the presence of chemical modification and lateral amino acid distribution in amino acid modified cellulose surfaces and as confirmation of the presence of individual amino acids on the fibrous networks of cellulose after chemical coupling. 170 Other researchers have used this method for verification of fatty acyl chain modification in modified CNMs. This was done by looking for characteristic peaks associated with the acyl chain-derived ions, which was used to indicate that fatty acids had been attached by covalent bonds to the fiber matrix.…”
Section: Secondary Ion Mass Spectrometry and Time Of Flight Simsmentioning
confidence: 99%
“…166 In literature, ToF-SIMS has been used to verify the presence of chemical modification and lateral amino acid distribution in amino acid modified cellulose surfaces and as confirmation of the presence of individual amino acids on the fibrous networks of cellulose after chemical coupling. 170 Other researchers have used this method for verification of fatty acyl chain modification in modified CNMs. This was done by looking for characteristic peaks associated with the acyl chain-derived ions, which was used to indicate that fatty acids had been attached by covalent bonds to the fiber matrix.…”
Section: Secondary Ion Mass Spectrometry and Time Of Flight Simsmentioning
confidence: 99%
“…The main advantage of oxidised BC is that various functionalities can be added to the material via carboxylic groups [15] [16] including; hydrophilic, aliphatic and aromatic amino acid groups [17]. Primary amino acid groups provide access for further modification such as preparing nanoparticles without any transfection reagents for easy cell uptake [18], strong antimicrobial activity that can be incorporated by attaching silver nanoparticles (AgNPs) [19] or amino alkyl groups [20] to the carboxylate groups.…”
Section: Introductionmentioning
confidence: 99%
“…Cateto et al [21] reported the functionalisation of BC with L-leucine using Fmoc-L-leucine and cellulose whiskers to enhance cell-adhesive structures, hydrophobic drug carriers and gas separation membranes. Kalaskar et al [17] reported the characterisation of cellulose fibre surfaces by modification using three different amino acids with variable side chain groups using solid phase peptide synthesis. Kalaskar and co-workers concluded that the size of the side chains of the amino acid has a direct effect on the final surface properties and chemical modification of cellulose fibres.…”
Section: Introductionmentioning
confidence: 99%
“…This has been achieved amongst others, due to the fact that the core level spectra of several cellulose-and lignin-based materials have been investigated by XPS in a multitude of studies, e.g. by Johansson et al (1999), Johansson and Campbell (2004), Belgacem et al (1995), Laine et al (1994), Stenius and Laine (1994), Andresen et al (2006Andresen et al ( ), Ö stenson et al (2006, Ding et al (2010) and Kalaskar et al (2010), to mention a few. However, there is a lack of knowledge concerning their molecular orbitals (distribution of the electrons) and valence band (VB) structures, meaning the density of electron states indicating the mobilities and binding strengths of the electrons.…”
Section: Introductionmentioning
confidence: 99%